MOLECULAR DOCKING STUDIES OF HYPEROSIDE AND BETA SITOSTEROL WITH HAEMOGLOBIN AS A TARGET FOR TYPE 2 DIABETES - M. UMA MAKHESWARI; DR. D. SUDARSANAM (International Journal of Pharma and Bio Sciences, 2013)
Diabetes mellitus, or simply diabetes, is a group of metabolic diseases having high blood sugar, either because the pancreas does not produce enough insulin, or because the cells do not respond to the insulin. Hyperoside, β-sitosterol was taken as ligand for molecular docking with Type 2 diabetic targets. Human haemoglobin protein whose crystallographic structures are available on the PDB database as 3PI1 was used for the docking analysis using the Schrodinger tool. The docking studies of the protein haemoglobin with two ligand hyperoside and β-sitosterol reveals that these are the good molecules which docks well with targets related to diabetes mellitus. Metformin is used as a standard drug for docking with haemoglobin. Hence hyperoside and β-sitosterol can be considered for developing into a potent antidiabetic drug.